Exercise technique: The push press - Bishop, C.; Chavda, S.; Turner, A. (Strength and Conditioning Journal, 2018)
The push press exercise has often been used by coaches as one of many tools to enhance an athlete's physical development. Recent research has further validated this exercise to augment power development. The aim of this paper is to outline the benefits this exercise has for strength and conditioning coaches.